Beginning SQL Server 2012 Administration - Walters, Rob.; Fritchey, Grant; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Beginning SQL Server 2012 Administration provides the essential skills and knowledge needed to begin a successful career as an SQL Server database administrator. It$1 (Bs an ideal book for those new to database administration, as well for those moving to SQL Server from other database brands such as Oracle and IBM DB2. SQL Server is more than just a database. It's situated within a larger context that includes solutions for reporting, for integrating data from other systems, for business intelligence and analysis, and more. Beginning SQL Server 2012 Administration paints the big picture to help you understand SQL Server$1 (Bs place in the grand scheme. Then you$1 (Bll move into the nuts and bolts of installing the product, learning the management tools at your disposal, creating your first database, and maintaining that database in an ongoing state of readiness. Beginning SQL Server 2012 Administration goes beyond teaching just the core competencies of effective database administration. You will also learn the latest trends in SQL Server such as virtualizing and consolidating of servers, and using SQL Server in the cloud as a service. Administrators experienced on other platforms will find insight from comparisons of key features between SQL Server and other platforms. Beginning SQL Server 2012 Administration lays an excellent foundation for success as an SQL Server database administrator. Provides the essentials of successful SQL Server administration Covers the latest trends such as virtualization and cloud computing Paints the big picture of Microsoft$1 (Bs data platforms
Keywords: Computer science; Database management; Computer Science; Database Management